The effect of a concept mapping Intervention on shared cognition and adaptive team performance over time - Santos, Catarina M. (2021)
Research has demonstrated the value of team adaptation for organizational teams. However, empirical work on interventions that teams can take to increase adaptive team performance is scarce. In response, this study proposes a concept mapping intervention as a way to increase teams’ ability to adapt following a task change. Particularly, this study examines the effect of a concept mapping intervention on team transition adaptation (the drop in performance after a change) and reacquisition adaptation (the slope of performance after the change) via its effect on task mental models and transactive memory systems. We conducted a longitudinal experimental study of 44 three-person teams working on an emergency management simulation. Findings suggest that the concept mapping intervention promotes reacquisition adaptation, task mental models, and transactive memory systems. Results also suggest that task mental models mediate the effect of the concept mapping intervention on reacquisition adaptation. A post hoc analysis suggests that the concept mapping intervention is only effective if it leads to high task mental model accuracy. Our study presents concept mapping as a practical intervention to promote shared cognition and reacquisition adaptation.